Happiness swings between free will and divine providence in Voltaire's novel " Zaidik or Destiny " - Hamood, Mohamed Yassir (Al-Adab Journal, 2022)
Happiness swing between free will and divine providence in the novel '' Zadig or destiny '' of Voltaire''Zadig or destiny '' is un oriental tale with Arabic names that stimulates the curiosity of orientalists who dine to discover those lands. The story is sequenced in twenty-one episodes that combine interest and pleasure. An impetus of endless amazing adventures that breed from each other like Russian dolls until they reach their ultimate goal that hero aspires to be happiness. Zadig has all the reasons for that, but his wealth, youth, handsomeness, and wit are powerless without the blessing of fate. Here lies the axis around which the episodes of the novel revolve. And the truth is that Voltaire took the risk of addressing the most complex philosophical questions ever. The subject includes many concepts as much as the number of creations on the surface of the universe, and worse than that is the absence of a common denominator between them. With the passage of time and the complexity of life and its interwining, the balance of this novel increases in the eges of those who cling to it as a palliative treatment. Moreover, '' Zadig or destiny'' transcends the boundaries of literature in order to enter the fields of philosophy, theology, sociology, as well as the science of morality and politics. But Voltaire, thanks to his art, and knowledge, was able to fly over it with ease and peace. The events of the novel revolve around three theaters, he events of the novel revolve around three theaters, starting with Babylon then Egypt, and ending with the Arabian Peninsula. Zadig endured various colors of torment and deceit from some ignorant people tried to betray him so that he would go to him, he was higher and loftier than those despicable and foolish behaviors, so he deals with his opponents with kindness and humanity the physician who cured their diseases without harming them. So, fate did justice to him, and heaven smiled at him, giving him the throne of Babylon, and the union with her venerable queen Astarta, whom he loved sincerely. Voltaire has declared his belief in one God who runs the universe wisely and justly. This infinite capacity which is beyond our perception controls humans' destiny. Besides, he perceives the relativity of free will and what is anticipated as a mere chance is not so. It is the verdict of Divine justice. The protagonist knew that the presence of evil is not free of charge, but sometimes it becomes a source of good. Finally, the tale of Honest or Fate is a serious message to get access to happiness and relief.The paper is divided into five subtopics:The east viewed by Voltaire.Modernity of topics of Voltaire.Search for happiness.Learning and educational adventures.Individual freedom and divine justice.Topic unity analysis was followed in doing the present paper.